(untitled) (AYUSHDHARA, 2025)
Balyadi lepa is a herbo-mineral formulation mentioned in the classical text called Yogaratnakara. It contains Shuddha Gandhaka, Shuddha Bhallataka, Shuddha Chitraka, Danti, Nimba, Vidanga, and Amlavetasa. Balyadi lepa is useful in the management of Switra. Balyadi lepa should be mixed with lukewarm water and applied on the affected area. Shodhana of Gandhaka is explained in Rasa Ratna Samucchaya, Shodana of Bhallataka and Chitraka is explained in Rasa Tarangin, preparation of Churna is explained in the Sharangadhara samhitha. In the present study, Churna of all drugs were taken in a Khalwa yantra and mixed well to prepare homogenous mixture of Balyadi lepa. Step by step pharmaceutical procedures were carried out according to classical reference and SOP. Loss during the process, total yield is noted. Pharmacological action of the Balyadi lepa is discussed in brief.